Quantum trajectory theory for a two-level atom in a squeezed vacuum field with non-radiative dephasing - Akram, Uzma; Wahiddin, Mohamed Ridza (Taylor and Francis, 1998)
The quantum trajectory theory is employed to study the decay of a two-level atom in a partial as well as a pure squeezed vacuum with non-radiative dephasing. We show that ensemble averages taken over a large number of trajectories are in perfect agreement with theoretical results. We find that single trajectories, however, reveal interesting features, which are not accessible by the theoretical approach. Specifically, single trajectories for one of the polarization quadratures of the atom damped by classical (|M| = N) and quantum (|M| = N(N + 1)) squeezed vacua reveal mostly coherent evolution in the latter. Resulting from this, the decay rate of the polarization quadrature for the quantum squeezed vacuum is slower than that for the classical squeezed vacuum.